New Insights Into the Polar Lipid Composition of Extremely Halo(alkali)philic Euryarchaea From Hypersaline Lakes - Bale, Nicole J.; Sorokin, Dimitry Y.; Hopmans, Ellen C.; Koenen, Michel; Rijpstra, W. Irene C.; Villanueva, Laura; Wienk, Hans; Sinninghe Damsté, Jaap S. (Frontiers in Microbiology, 2019)
We analyzed the polar membrane lipids of thirteen strains of halo(alkali)philic euryarchaea from hypersaline lakes. Nine belong to the class Halobacteria, representing two functional groups: aerobic polysaccharide utilizers and sulfur-respiring anaerobes. The other four strains represent halo(alkali)philic methanogens from the class Methanomicrobia and a recently discovered class Methanonatronarchaeia. A wide range of polar lipids were detected across the 13 strains including dialkyl glycerol diethers (archaeols), membrane-spanning glycerol tetraethers and diether-based cardiolipins. The archaeols contained a range of core lipid structures, including combinations of C20 and C25 isoprenoidal alkyl chains, unsaturations and hydroxy moieties. Several diether lipids were novel, including: (a) a phosphatidylglycerolhexose (PG-Gly) headgroup, (b) a N,N,N-trimethyl aminopentanetetrol (APT)-like lipid with a methoxy group in place of a hydroxy group on the pentanetetrol, (c) a series of polar lipids with a headgroup with elemental composition of either C12H25NO13S or C12H25NO16S2 and (d) novel cardiolipins contained a putative phosphatidylglycerolphosphate glycerophosphate (PGPGP) polar moiety. We found that the lipid distribution of the thirteen strains could be generally separated into groups, the methanogens (group) and the Halobacteria (class) based on the presence of specific core lipids. Within the methanogens, adaption to a high or more moderate salt concentration resulted in different ratios of glycerol dialkyl glyc¬erol tetraethers (GDGTs) to archaeol. The methanogen Methanosalsum natronophilum AME2T had the most complex diether lipid composition of any of the thirteen strains, including hydroxy archaeol and macrocyclic archaeol which we surmise is an order-specific membrane adaption. The zwitterionic headgroups APT and APT-Me were detected only in the Methanomicrobiales member Methanocalculus alkaliphilus AMF2T which also contained the highest level of unsaturated lipids. Only alkaliphilic members of the Natrialbales order contained PGPGP cardiolipins and the PG-Gly headgroup. The four analyzed neutrophilic members of the Halobacteria were characterized by the presence of sulfur-containing headgroups and glycolipids. The presence of cardiolipins with one or more i-C25 alkyl chains, generally termed extended archaeol (EXT-AR), in one of the Methanonatronarchaeia strains was unexpected as only one other order of methanogenic archaea has been reported to produce EXT-AR. We examined this further by looking into the genomic potential of various archaea to produce EXT-AR.